2022
DOI: 10.1038/s41598-022-11887-1
|View full text |Cite
|
Sign up to set email alerts
|

Solubility measurement and thermodynamic modeling of pantoprazole sodium sesquihydrate in supercritical carbon dioxide

Abstract: Knowing the solubility data of pharmaceutical compounds in supercritical carbon dioxide (ScCO2) is essential for nanoparticles formation by using supercritical technology. In this work, solubility of solid pantoprazole sodium sesquihydrate in ScCO2 is determined and reported at 308, 318, 328 and 338 K and at pressures between 12 and 27 MPa. The solubilities are ranged between 0.0301 $$\times$$ × 10–4 and 0.463 $$\times$$ × 10–4 in mole fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The experimental data on the solubility of solid solutes in supercritical carbon dioxide was collected from a wide range of literature sources. ,, …”
Section: Methodsmentioning
confidence: 99%
“…The experimental data on the solubility of solid solutes in supercritical carbon dioxide was collected from a wide range of literature sources. ,, …”
Section: Methodsmentioning
confidence: 99%
“…In practice, however, the dissolution process is treated as a chemical reaction from which the Chrastil model 17 is oen used to estimate the solubility variations. [18][19][20][21][22][23] It can be concluded that there is not sufficient evidence to classify the sulfur dissolution in natural gas as a chemical or a physical process.…”
Section: Introductionmentioning
confidence: 99%
“…However, acquiring solubility data under the necessary pressure and temperature circumstances is a difficult process. Thus, modelling is important for solubility data interpolation [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…The first model needs the compounds' physical characteristics, such as vapour pressure, molar volume, critical properties, and acentric factor. The equation of state modelling would be quite beneficial if it had all the required physical characteristics [13]- [15]. Unfortunately, many compounds lack the necessary property data.…”
Section: Introductionmentioning
confidence: 99%